Development of Folk-Dance Videos for E-learning - Llupar, Mikee L.; Malones, Lorie Jean L.; Sombria, Alden Jay F.; Calixtro, Vivencio L. (Universitas Pendidikan Indonesia (UPI), 2022)
This study was geared towards the development of folk-dance videos for e-learning through folk dance tutorial videos for physical education instructors and folk-dance trainers/choreographers to determine the level of development in terms of acceptability, usability, and relevance. The study utilized a descriptive survey design which allows us to reveal the level of development of the developed folk dance videos for e-learning. We also developed a dance that had been used as a video tutorial wherein we have performed and recorded for the respondents to follow. A survey questionnaire was done to know what is the level of development of the developed and validated folk dance videos for e-learning. Findings revealed that the folk-dance videos for e-learning developed by we are excellent and meet above 75-90% acceptability, usability, and relevance standards. This study can conclude that the developed videos for e-learning were an effective tool in teaching dance to the students wherein the developed videos are acceptable, useful and relevant. It gives opportunity for the physical education instructors and folk-dance trainers/choreographers to have their time to develop their dance skills and it would lessen their task to teach students because the video is pre-recorded and their students can learn from it without them physically.